Renaissance Futurities Science, Art, Invention - Villaseñor Black, Charlene; Álvarez, Mari-Tere (University of California Press, 2019)
"Open access to this title is possible thanks to the generous support of Arcadia, a charitable fund of Lisbet Rausing and Peter Baldwin. Renaissance Futurities considers the intersections between artistic rebirth, the new science, and European imperialism in the global early modern world. Charlene Villaseñor Black and Mari-Tere Álvarez reconsider the work of Renaissance genius Leonardo da Vinci (1452-1519), prolific artist and inventor, and other polymaths such as philosopher Giulio "Delminio" Camillo (1480-1544), physician and naturalist Francisco Hernández de Toledo (1514-1587), and writer Miguel de Cervantes (1547-1616). This concern with futurity is inspired by the Renaissance itself, a period defined by visions of the future, as well as by recent theorizing of temporality in Renaissance, queer, and ethnic studies. This transdisciplinary collection is at the cutting edge of the humanities, the sciences, and the arts with contributions in history, art history, literature, media studies, mathematics, and medicine. "A superb provocation, asking us to reimagine the Renaissance in both space and time, resituating it at the crossroads of Europe and its early modern empires; of art, technology, and science; and of alternative pasts and futures." TARA NUMMEDAL, author of Anna Zieglerin and the Lion's Blood: Alchemy and End Times in Reformation Germany "This volume approaches the field through the unique lens of futurity, bringing together an eclectic transdisciplinary group of scholars who focus on ingenuity and futuristic thinking in various Renaissance contexts." PAULA DeVOS, Professor of History, San Diego State University CHARLENE VILLASEÑOR BLACK is Professor of Art History and Chicana/o Studies at the University of California, Los Angeles. MARI-TERE ÁLVAREZ is Associate Director of the University of Southern California's International Museum Institute."